Sistem Informasi Manajemen Pasien Fisioterapi Pada Klinik Maha Bhoga Marga - I Wayan Widi Karsana; Putu Andhika Kurniawijaya (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Maha Boga Marga Clinic is one of the community health service centers that provides various health services including general health services, dental health services, health education, elderly health services and physiotherapy services. The physiotherapy service unit at the Maha Boga Marga clinic has served many patients undergoing physiotherapy therapy and rehabilitation, which are handled by professionals. Several obstacles were found in providing services to physiotherapy patients, where data management of physiotherapy patients was still done manually by writing on paper forms. Starting from patient registration, diagnosis and medical treatment results are all recorded in the report book so that it will be difficult for officers to track patient data, both diagnoses and treatments that have been carried out. This greatly reduces services to physiotherapy patients because it takes a long time to find data. It is hoped that a computerized recording system will make it easier for officers to track medical record data for physiotherapy patients. and communication, which is expected to help the physiotherapy service unit at the Maha Boga Marga clinic in providing health services to physiotherapy patients.